%%f(x)=-\frac14x^2+6x-11%%

%%f(x)=-\frac14x^2+6x-11%%

%%\hphantom{f(x)}=-\frac14\left(x^2-24x\right)-11%%

%%\hphantom{f(x)}=-\frac14\left(x^2-2\cdot12x+12^2-12^2\right)-11%%

Multipliziere die Klammer aus.

%%\hphantom{f(x)}=-\frac14\left(x^2-2\cdot12x+12^2\right)+36-11%%

Fasse zusammen.

%%\hphantom{f(x)}=-\frac14\left(x^2-2\cdot12x+12^2\right)+25%%

Fasse zur 2. binomischen Formel zusammen

%%\hphantom{f(x)}=-\frac14\left(x-12\right)^2+25%%

Lies den Scheitelpunkt ab.

%%\Rightarrow S=\left(12|25\right)%%